Analisis Keterampilan Proses Sains Peserta Didik Kelas IX SMP Se-Kecamatan Tamalate pada Materi Struktur dan Fungsi Jaringan Tumbuhan - Ana Seftia Andriani; Ramlawati Ramlawati; Muhammad Aqil Rusli (Universitas Negeri Makassar, 2023)
This research aims to determine: (1) the levels of science process skills students of SMP grade-IX in Tamalate District and (2) description of science process skills students of SMP grade-IX in Tamalate District. The research method is descriptive quantitative with descriptive survey research design. The population in this research were 1,677 students from 5 schools with A accredited namely SMPN 15 Makassar, SMPN 18 Makassar, SMPN 24 Makassar, SMPN 26 Makassar and SMPN 27 Makassar with selected samples using the Slovin Formula by Random Class Sampling so that a sample of 413 students was obtained. The research instrument is a test of science process skills in the form of multiple choice as many as 24 questions that have been validated by experts. Data collection techniques in this research is multiple choice tests scored 1 for correct answers and 0 for wrong answers. Data were analyzed by descriptive statistical analysis. Based on the results of data analysis, it is known that: (1) the level of science process skills students grade-IX of SMPN in Tamalate District at the enough category with the average score of 12.09 by 50.8% and (2) description of science process skills students grade-IX of SMPN in Tamalate District on observing indicators 58% (Good), classifying indicators 53, 35% (Enough), predicting indicators 52.13% (Enough), communicating indicators 58.03% (Good), makes a hypothesis indicators of 50.04% (Enough), the indicator determining the variable 40.76% (Low) and the indicator designs the experiment 34.43% (Low) and on concluding indicators 52% (Enough).